2015
DOI: 10.1155/2015/476383
|View full text |Cite
|
Sign up to set email alerts
|

Replanning Criteria and Timing Definition for Parotid Protection-Based Adaptive Radiation Therapy in Nasopharyngeal Carcinoma

Abstract: The goal of this study was to evaluate real-time volumetric and dosimetric changes of the parotid gland so as to determine replanning criteria and timing for parotid protection-based adaptive radiation therapy in nasopharyngeal carcinoma. Fifty NPC patients were treated with helical tomotherapy; volumetric and dosimetric (D mean, V 1, and D 50) changes of the parotid gland at the 1st, 6th, 11th, 16th, 21st, 26th, 31st, and 33rd fractions were evaluated. The clinical parameters affecting these changes were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
5
37
0
Order By: Relevance
“…And a previous study reported a similar result, with the accumulative average D mean increasing of 11.38% at the end of radiation therapy for all enrolled parotid glands with helical tomotherapy [18]. The sharp increase of the average D mean per fraction for the left parotid gland could be caused by the location of the primary tumors, which were mostly (8/13) located on the left side of the body.…”
Section: Discussionsupporting
confidence: 67%
“…And a previous study reported a similar result, with the accumulative average D mean increasing of 11.38% at the end of radiation therapy for all enrolled parotid glands with helical tomotherapy [18]. The sharp increase of the average D mean per fraction for the left parotid gland could be caused by the location of the primary tumors, which were mostly (8/13) located on the left side of the body.…”
Section: Discussionsupporting
confidence: 67%
“…Treatment plan adaptation in the re-planning situation was evaluated for head and neck cases by several groups [ 10 12 ]. The aim was to determine re-planning criteria and timing for plan adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive RT can potentially decrease radiation dose to normal organs and thereby reduce xerostomia and nausea. 2630 …”
Section: Discussionmentioning
confidence: 99%